2020
DOI: 10.20944/preprints202007.0197.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How Can We Improve the Consumption of a Nutritionally-Balanced Maternal Diet in Rural Bangladesh? The Key Elements of the ‘Balanced Plate’ Intervention

Abstract: Social, cultural, environmental and economic factors closely regulate the selection, allocation and consumption of maternal diets. We developed a nutrition behaviour change intervention to promote a balanced diet in pregnancy through practical demonstration in rural Bangladesh and tested the impact with a cluster randomised controlled trial. This paper presents the findings of the process evaluation and describes the strategies that worked for intervention compliance. We conducted in-depth interviews w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…The process evaluation of the trial 30 provided insights into why the intervention was so impactful. It identified key elements in the intervention strategy, such as practical demonstration of portion sizes; addressing local food perceptions; demystifying animal-source foods; engaging husbands and mothers-in-law; leveraging women’s social networks; and harnessing community health workers’ social role, that played a crucial role in achieving the desired adherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process evaluation of the trial 30 provided insights into why the intervention was so impactful. It identified key elements in the intervention strategy, such as practical demonstration of portion sizes; addressing local food perceptions; demystifying animal-source foods; engaging husbands and mothers-in-law; leveraging women’s social networks; and harnessing community health workers’ social role, that played a crucial role in achieving the desired adherence.…”
Section: Discussionmentioning
confidence: 99%
“…The process evaluation of the trial 30 provided insights into why the intervention was so impactful. It identified key elements in the intervention strategy that was crucial in achieving the desired adherence.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative evaluation of a nutrition intervention in Bangladesh identified that education about equitable-food distribution (a context-specific, cultural practice) was a critical component of the intervention. 12…”
Section: Healthmentioning
confidence: 99%
“…18 When used to train pregnant women in rural Bangladesh, these nutritional plates support improvements in portion sizes and dietary diversity. Family members of the women are also shown to have begun to consume a healthier diet (Alam et al, 2020). The second is the nutrition programs in workplaces, such as garment factories in which the majority of employees are women.…”
Section: Illustrative Examplesmentioning
confidence: 99%